Effectiveness of Class IC Antiarrhythmics in Patients with Paroxysmal Form of Atrial Fibrillation in Absence of Structural Heart Disease - D. A. Tsaregorodtsev; M. A. Khalikova; S. S. Vasyukov; M. M. Beraya; A. V. Sedov (Рациональная фармакотерапия в кардиологии)
Aim. To study the efficacy of class IC arrhythmic drugs (AAD) and catheter ablation (CA) for paroxysmal form of atrial fibrillation (AF) in patients with without structural heart disease.Material and methods. The study included 122 patients (44 men, 78 women, mean age 63 [55;68] years) with symptomatic AF paroxysms. Patients was divided into the lappaconitine hydrobromide group (LH group; n=26), the propafenone group (P group; n=25) – 25 patients, the diethylaminopropionylethoxycarbonylaminophenothiazine hydrochloride (DH group; n=23), the CA groups: radiofrequency ablation (RFA group; n=24) and cryoballoon ablation (CRYO group; n=24) groups each included 24 patients. The primary endpoint was the AF recurrence within 6 and 12 months from the onset of antiarrhythmic drug therapyand in RFA and CRYO groups – within 6 and 12 months after the end of the blinding period. Additionally, in AAD groups a composite endpoint was assessed: the frequency of recurrence of AF within 6 months and the frequency of side effects requiring drug withdrawal.Results. Within the 6 months AF recurrence was observed in 13 (50%) patients of the LH group, 11 (44%) patients of the P group, and 13 (56.5%) patients of the DH group (p=0.687). Side effects requiring drug withdrawal were observed in the LH group in 2 patients (7.7%), in the P group in 3 patients (12%) and in the DH group in 3 patients (13%) (p=0.801). The difference in frequency of reaching the composite endpoint was not significant (p = 0.581) and the incidence was 57.7%, 56%, 69.5%, respectively in groups LH, P and DH. The efficacy of CA was higher than class IC AADs: 77% vs 39% (that including the withdrawals of AADs due to side effects) (p˂0.001). At the same time, there was no significant difference in the effectiveness of RFA and CRYO: AF recurrences within 6 months after the end of the blinding period were registered in the RFA group in 29% of cases, in the CRYO group – in 16.7% of cases (p=0.247). The overall effectiveness of CA after 12 months was 69%, which was significantly higher than the effectiveness of AADs that was 38% (p˂0.001).Conclusion. Starting the AAD therapy with IC class in patients with paroxysmal AF in the absence of structural pathology, despite acceptable safety, one should take into account that, regardless of the initially prescribed drug, less than half of patients can achieve prevention of AF recurrence within 1 year. CA for AF can be considered as a first line therapy or can be recommended if one of IC class AADs is ineffective.